Preselection in the digital age: A comparison of perceptions of asynchronous video interviews with online tests and online application documents in a simulation context - Johannes M. Basch; Klaus G. Melchers; Julia C. Büttner (International Journal of Selection and Assessment, 2022)
Asynchronous video interviews (AVIs) are increasingly used to preselect applicants. Previous research found that interviewees are more skeptical of these interviews compared to other forms of interviews. However, comparing AVIs to other interviews is not completely appropriate because of their lack of interactivity and their use during earlier stages of the selection process. Therefore, we compared perceptions of AVIs with perceptions of other preselection tools (online cognitive ability tests and online application documents). Compared to other preselection instruments, potential applicants do not have more skeptical fairness perceptions of AVIs. However, we found differences for perceived usefulness, perceived ease of use, privacy concerns, and perceptions of organizational attractiveness. Organizations can take this into account when choosing how to preselect their applicants.
Keywords: 650; applicant reactions; asynchronous video interviews; personnel selection; preselection; selection interviews